2009
DOI: 10.1088/0953-8984/21/28/285301
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic properties of maghemite (γ- Fe2O3) nanocrystalline quantum dots determined by electrophoretic deposition

Abstract: We applied a DC electric field between two flat electrodes to attract thermally charged maghemite (γ-Fe(2)O(3)) nanocrystalline quantum dots dissolved in hexane to form smooth, robust, large area and apparently identical films of equal thickness on both electrodes. Visible microscopy, scanning electron microscopy, atomic force microscopy and profilometry showed that the electrophoretically deposited dot films were very smooth with an rms roughness of ∼10 nm for ∼0.2 µm thick films. The films were of high quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Hence, a proper, thermodynamic understanding of this preferential charging requires a view on the countercharge. Third, this work shows that charges are present in QD dispersions in apolar solvents, yet it does not address possible mechanisms of charge generation, which is clearly of importance for applications where rapid charging or discharging is important, such as electrophoretic deposition , or (avoiding of) photoionization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hence, a proper, thermodynamic understanding of this preferential charging requires a view on the countercharge. Third, this work shows that charges are present in QD dispersions in apolar solvents, yet it does not address possible mechanisms of charge generation, which is clearly of importance for applications where rapid charging or discharging is important, such as electrophoretic deposition , or (avoiding of) photoionization.…”
Section: Discussionmentioning
confidence: 99%
“…An aspect of these colloidal NP dispersions in apolar solvents that systematically returned in the literature is that of dipoles or charges on the NPs. ,, Using an apolar solvent (2,2,4,4,6,6,8-heptamethylnonane) and excess free ligand to stabilize the dispersion, Shim et al . showed that dispersions of CdSe QDs in apolar solvents have a nonzero conductivity, a result they related to charges on the QDs.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, EPD conducted on nanocrystals that were suspended in nonpolar solvents has increased in popularity, in contrast to the more traditional approach of using polar solvents (methanol, acetone, water, etc.) to produce films, coatings, and casts. Two of the driving factors for using nonpolar solvents are: 1) to suppress the van der Waals interactions between nanocrystals while in suspension, which frequently results in particle agglomeration or aggregation before the nanocrystals reach the electrode; and 2) to minimize electrolysis of the suspension solvent, which leads to difficult-to-control hydrodynamics and electrohydrodyamics of the suspension.…”
Section: Introductionmentioning
confidence: 99%